Ocorrência e aspectos bioecológicos dos curculionídeos-das-raízes em soja [Glycine max (L). Merryl] - Bortolotto, Orcial Ceolin (2008)
The objective of this study was to evaluate the population fluctuation and the distribution of the soybean root weevils (Coleoptera: Curculionidae), and the population fluctuation was determined in a soybean area in the period December, 2006 to November, 2007, in the Restinga Seca county, RS. Distribution in space and time was evaluated in a soybean experimental area in 2006-2007 at UFSM. Twenty trenches with a dimension of 0.25 m2/unit were made every two weeks for evaluation of larvae and pupae population fluctuation and 105 trenches with the same dimension were made to determine larvae distribution. To evaluate population of adults, ten emergency cages of 2.00 m2/unit were used. Adults distribution was evaluated weekly with four cloth stroke in each of the 105 sampling points of the soybean area. Larvae were found almost during the 12 months period of evaluation. They were scarce from October to November, 2007, however, predominate medium and large sizes (3rd and 5th instars, respectively). 74 % of the larvae population found concentrated in the first 0. 10 m of depth in the soil. A population peak was observed in February 2007, with a population of 16 larvae/m2 including mainly 1st and 2nd instars. Only naupactini belonging to the species Naupactus purpureoviolasceus were collected in the cages for adults. A typical aggregated distribution for a soil insect was observed in this study. Pupae phase was observed as temperature raise in early spring and last about four weeks. Adults emerged in spring and summer, with higher populations from October to January. Adults of soybean root weevils were initially located at the edge of the soybean field, but they had an aggregated distribution from the first point of occurrence. The genera Naupactus e Pantomorus were predominant in the soybean area of Santa Maria, with six species being identified in this study. Adults sampling is recommended as a tool to predict the occurrence of larvae in the coming soybean season.